Central venous catheters for out-patient management of malignant disorders. Issue 8 (August 1983) - Stockwell, M; Adams, M; Andrew, M; Cameron, G; Pai, K
Abstract : The use of tunnelled central venous catheters in children with malignant disorders is an effective and safe way of giving out-patient chemotherapy and supportive care. The benefits include ready venous access, ease of administration of chemotherapy, decreased time spent in the out-patient clinic, and less anticipatory vomiting and emotional trauma for patients, parents, and staff.